The Effect of Internal Control Components on Mitigating the Impact of COVID-19 Risks in Healthcare Organizations in Ethiopia - Enyew Mulu Zelie (Universitas Hayam Wuruk Perbanas, 2020)
The COVID-19 pandemic hit the world’s economy and created significant risks from which many sectors, including the healthcare sector, are adversely affected. This study is aimed to evaluate the reliability of internal control systems in healthcare organizations and the effect of internal control components on mitigating the impacts of risks created by the pandemic. The study used a cross-sectional primary data collected from 241 healthcare organizations in Addis Ababa, Ethiopia. Descriptive statistics and ordered logistic regression analysis methods was applied. Internal control system in the Ethiopian healthcare organizations is found to be moderately reliable. In addition, the ordered logistic regression results show that control environment, risk assessment, control activities, information and communication, and monitoring activities have a statistically significant and negative effect on impact of COVID-19 risks. This implies as the reliability of internal control components increases, the impact of COVID-19 risks on the overall performance of healthcare organizations decreases.